(untitled) (Iranian Journal of Kidney Diseases, 2022)
Renal sarcoidosis frequently causes granulomatous interstitial nephritis, but clinically relevant nephritis is uncommon. IgA nephropathy caused by sarcoidosis is usually associated with milder stages of renal dysfunction, and only one case of rapidly progressive IgAN has been reported to date. We present an interesting case of a patient with a rapidly progressive form of IgA nephropathy caused by sarcoidosis that was successfully treated. DOI: 10.52547/ijkd.7027